A THE ROAD TO MIGRATION: CIVILIZATION AND SUPPLY BASED CONFLICT - Tibor, Ferenc Szavai (International Scientific Journal Vision, 2018)
Currently Europe is living through a modern age migration, even though the phenomenon of migration was already present in the 19-20 century economic history. However the size and composition of the current migration diff ers considerably from those of the past. On the one hand after the Cold War the confl ict of nation-states became insignifi cant, the clash of civilizations characterizes our time. Decrease in population, dissolution of states and fi ght for provision make the life of the people uncertain. Available supplies are being depleted, and developed countries are needing workforce. No civilization has found an antidote to these problems.